Cytotoxicity evaluation of Pro Root MTA, Root MTA and Portland Cement (PC) on L929 mouse fibroblasts - Sharifian MR; Zarrabian M; Razmi H; Ghobadi M; Kharrazifard MJ; Hemmatzadeh F; Afzalifar R (Tehran University of Medical Sciences, 2007)
Background and Aim: Mineral Trioxide Aggregate (MTA) is a material used in many endodontic problems. Recently a number of studies, have reported that Portland Cement (PC) and MTA have similar physical, chemical and biologic properties. In addition, a material known as Root MTA which is produced in Iran has been claimed to have similar properties to Pro Root MTA. If these claims are true, possible use of PC and Root MTA in clinic instead of Pro Root MTA will be quite cost effective. The aim of this study was to investigate the toxicity of Pro Root MTA, Root MTA and Portland Cement on L929 mouse fibroblasts.Materials and Methods: In this experimental study 0, 4, 24 hours and 7 days' extracts of materials were transferred to cell culture plates containing L929 fibroblasts. After 24 hours incubation, cells were stained by Neutral Red (NR), and optical density (OD) of each cell was read with ELISA reader. Data were analyzed using Tukey HSD and one way analysis of variance. P<0.05 was considered as the level of significance.Results: In all surveyed groups and negative control group, at all time points separated cells from the base of the well were round. Refraction which is a characteristic of cellular death was not observed, whereas the separated cells from the base of well in positive control group showed refractional characteristic.Conclusion: Based on the findings of this study Pro Root MTA, PC and Root MTA have the same biocompatibility. PC seems to have the potential to be used in the same clinical situation as MTA. However in order to replace MTA with these less expensive materials more in vitro and in vivo studies are suggested.